PENA PRIVATIVA DE LIBERTAD DE 40 AÑOS PARA EL DELITO DE VIOLACIÓN Y MUERTE EN LOS MENORES DE 14 AÑOS - Dueñas Zhamungui, Karla Vanessa (2020)
This thesis constitutes the final report of my investigative process motivated in Ecuador by the Comprehensive Organic Criminal Code, in its article 171 numeral 3 stipulates "It is violation of the Constitution of the Republic of Ecuador, carnal access, with total or partial introduction of the virile member, orally, anally or vaginally; or the introduction, vaginally or anally, of objects, fingers, or organs other than the virile member, to a person of any sex. Whoever commits it, will be punished with a sentence of imprisonment of nineteen to twenty-two years in any of the following cases: numeral 3: "When the victim is under fourteen. In all cases, if the victim's death occurs, he will be punished with imprisonment from 22 to 26 years " The rule in article 76 numeral 6, which guarantees "due proportionality between infractions and criminal penalties" Therefore, the current norm does not establish due proportionality according to the crime committed as rape and death in the victim under 14 years. I believe that the penalty is not the maximum penalty for the aggressor who, due to his superiority status, abuses such power against the child when he is seen in a situation of vulnerability and defenselessness, penalizing the crime of rape against a child under 14 years of age and provoking his death with imprisonment of 40 years, without mitigating benefit for the infraction he commits by injuring and violating the legal good protected by the Constitution such as the life and sexual integrity of the minor